ON-ICE trial: investigation of the combined effects of oxytocin and naltrexone on stress-induced and alcohol cue-induced craving in alcohol use disorder-Study protocol of a phase II randomised double-blind placebo-controlled parallel-group trial - Vetter, Sina; Thomas, Bettina C.; Krisam, Johannes; Limprecht, Ronald; Klose, Christina; Stenger, Manuel; Pourbaix, Madeleine; Ries, Marcel; Vollstädt-Klein, Sabine; Koopmann, Anne; Lenz, Bernd; Kiefer, Falk; et al. (BMJ open, 2022)
Introduction Although alcohol dependence (AD) is highly prevalent, only few medications are approved for its treatment. While currently approved medications, such as naltrexone (NTX), reduce craving and relapse risk to a certain extent, new approaches are needed to complement these pharmaca. One potential compound is oxytocin (OXY), which proved beneficial effects on alcohol craving and stress reactivity in preliminary clinical studies and synergism with NTX effects. - Methods and analysis This clinical phase II trial is a monocentre two-armed, placebo (PLC)-controlled, 1:1 randomised, double-blind, parallel-group study. 62 participants with AD will be randomised to receive either intranasal OXY spray (24 IU) or PLC spray plus oral NTX (50 mg) for 2 days, and alcohol craving will be assessed using a validated combined stress-exposure and cue-exposure experiments and MRI. The primary outcome will be the intensity of alcohol craving, assessed using the Alcohol Urge Questionnaire (AUQ), 60 min after OXY/PLC application, directly after the stress and cue exposures. Secondary outcomes include subjective stress, negative affect, cortisol and OXY plasma levels, and neural response to alcohol and emotional cues and natural rewards. Follow-up drinking data were collected over 90 days. The primary efficacy analysis will test the difference between the verum and the PLC group in the distribution of AUQ craving scores. Appropriate statistical analysis will be used for the evaluation of the secondary outcomes. - Ethics and dissemination This trial has been approved by the ethics committee of Heidelberg University and competent authority. All participants in the trial will provide written informed consent. The study will be conducted according to the principles of the Declaration of Helsinki and in accordance to the German Medicinal Products act. Results of this study will be disseminated in peer-reviewed scientific journals and deidentified data, and the statistical analysis plan will be made available via open-access online repositories. - Trial registration numbers EudraCT 2021-003610-40 and NCT05093296.